Clinical Features and Magnetic Resonance Imaging Findings in 7 Dogs with Central Nervous System Aspergillosis. (16th October 2015) - Taylor, A.R.; Young, B.D.; Levine, G.J.; Eden, K.; Corapi, W.; Rossmeisl, J.H.; Levine, J.M.
Abstract : Background: Systemic aspergillosis is a manifestation of Aspergillus sp. infection that can result in central nervous system (CNS) involvement with marked alterations in CNS function. Information regarding the clinical presentation and magnetic resonance imaging (MRI) findings in cases of aspergillosis with CNS involvement is lacking, resulting in a need for better understanding of this disease. Hypothesis/Objectives: The primary objectives were to describe the clinical features and MRI findings in dogs with CNS aspergillosis. The secondary objectives were to describe clinicopathologic findings and case outcome. Animals: Seven dogs with CNS aspergillosis. Methods: Archived records from 6 institutions were reviewed to identify cases with MRI of CNS aspergillosis confirmed with serum galactomannan enzyme immunoassay (EIA) testing, culture, or supported by histopathology. Signalment, clinical, MRI, clinicopathologic, histopathologic, and microbiologic findings were recorded and evaluated. Results: Aspergillosis of the CNS was identified in 7 dogs from 3 institutions. The median age was 3 years and six were German Shepherd dogs. Five dogs had signs of vestibular dysfunction as a component of multifocal neurological abnormalities. The MRI findings ranged from normal to abnormal, including hemorrhagic infarction and mass lesions. Conclusions and Clinical Importance: Until now, all reported MRI findings in dogs with CNS aspergillosis have been abnormal. We document that CNS aspergillosis in dogs, particularly German Shepherd dogs, can be suspected based on neurologic signs, whether MRI findings are normal or abnormal. Confirmatory testing with galactomannan EIA, urine, cerebrospinal fluid (CSF) or tissue culture should be performed in cases where aspergillosis is a differential diagnosis.